Structured Assessments: Enhancing Success in Early Nursing Education and Student Retention. - Park, Esther O.; Chang, Kathleen; Koduah, Susan (Nursing Reports, 2025)
Background: High attrition rates among nursing students, particularly during the sophomore year, threaten the sustainability of the nursing workforce. Objectives: This study assessed structured assessment methods implemented at a School of Nursing located in northern Virginia to improve student success and reduce attrition. Methods: Interventions included a three-tier grading system (Mastery, Intermediate, and Novice), standardized rubrics, detailed instructor guidelines, remediation sessions, and medication competency practice materials. Results: Data from student and instructor feedback surveys and attrition rate comparisons between Spring 2024 and Spring 2025 revealed a reduction in overall attrition of sophomores from 23.5% to 17.3% and from 20% to 12% in the Fundamentals courses. Students reported increased engagement and confidence in foundational core skills, though complex nursing skills care posed challenges. Instructors valued the structure but questioned the suitability of certain skills for sophomores. Conclusions: These findings underscore the value of structured assessments in enhancing retention, with implications for revision of curriculum design in students' early years of nursing education.